Electrospun alginate nanofibres as potential bio-sorption agent of heavy metals in water treatment - T. C. Mokhena; N. V. Jacobs; A. S. Luyt (eXPRESS Polymer Letters)
This paper reports on the potential of electrospun alginate nanofibre membranes to be used for the bio-sorption of heavy metals from aqueous solutions. Poly(ethylene oxide) (PEO) and its blends were electrospun at an applied voltage of 1–1.3 kV/cm and a solution flow rate of 0.8 mL·hr–1. The electrospinnability of the nanofibre blends was enhanced by storing the blend solutions in a controlled environmental chamber. The electrospun nanofibre membranes were washed with calcium chloride to remove PEO. Beadless nanofibres with average diameters of 114 nm and a surface area of 18.03 m2·g–1 were obtained. Fourier transform infra-red (FTIR) spectroscopy and thermogravimetric analysis (TGA) confirmed the removal of PEO after washing with calcium chloride. The adsorption behaviour of the nanofibrous membranes was investigated using Cu(II) as model metalloid at different concentrations (0–1000 mg·L–1), temperatures (25, 40, and 60 °C) and pH values (2–6). The Langmuir isotherm better presented the equilibrium experimental data than the Freundlich model. The electrospun alginate membranes displayed a maximum monolayer sorption capacity (Q0) of 15.6 mg·g–1 at a pH of 4. In a competitive adsoption experiment the removal of metal ions in a mixture followed the order Cu > Ni > Cd > Co.